Identifying rice varieties for mitigating methane and nitrous oxide emissions under intermittent irrigation - Loaiza, Sandra; Verchot, Louis; Valencia, Drochss; Costa Jr, Ciniro; Trujillo, Catalina; Garcés, Gabriel; Puentes, Oscar; Ardila, Jorge; Chirinda, Ngonidzashe; Pittelkow, Cameron (Elsevier, 2024)
Most of the research evaluating rice varieties, a major global staple food, for greenhouse gas (GHG) mitigation has been conducted under continuous flooding. However, intermittent irrigation practices are expanding across the globe to address water shortages, which could alter emissions of methane (CH